The land question - Chase, W. B. (My University, 1897)
Introduction: The land question is essentially a question of the equality of opportunity. Men to possess equality of opportunity must have equal rights to the materials and forces of nature. Land includes all the natural materials and forces of the universe outside of man. Without land men can make nothing and trade nothing, neither artificial materials and appliances nor the finished objects to be consumed. It is his standing place, his natural workshop, the storehouse from which he draws everything required for ministering to the satisfaction of his material wants. To invert one person, therefore, with exclusive ownership of the land, or to recognize and enforce the claims of one man to such ownership—whether his claims originate in force, fraud or contract—would be equivalent to conferring upon him absolute power over other men. In respect to this power, it would make no difference whether exclusive ownership of all land were vested in one man or in many, provided the owners were few enough to combine and agree among themselves, and should actually do so. It is not until the number of land owners becomes large as to make unity of decisions and actions impracticable, or until for any other reason they cease to act together as one man, that a difference may be distinguished; and then the difference in one degree and not of principle.
Citation: Chase, W. B. The land question. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Land; Ownership; Colonization; Political science; Economics; Government; Theses; Manuscripts (documents)